Multi-channel wireless sensor network for Heavy-Lift Launch Vehicles. (May 2019) - Chalhoub, Gerard; Deux, Marie-Caroline; Rmili, Badr; Misson, Michel
Abstract: A typical new generation Heavy-Lift Launch Vehicle (HLV) has more than 600 sensors on board. More than 80% of these sensors are used for non-critical operational and technological data. This data is sent to the ground launching controllers allowing them to supervise, in real time or a posteriori, information concerning the state of the HLV and the progress of the launching operation. Sensors are traditionally connected to a concentrator entity using cables. The concentrator is a special node in charge of collecting data that is generated by sensors and transmit it to the ground controllers unit. The use of wireless technology to interconnect sensor nodes with the concentrator would allow an ease of deployment and a weight gain which will help achieve assembly time reduction and a gain in terms of generated power. Nevertheless, of-the-shelf wireless technologies cannot guarantee a wired equivalent reliability in terms of packet delivery ratio or end-to-end delay. Indeed, when transmitting over wireless communication links it is challenging to find a solution that avoids data loss especially in high data rate scenarios. This is essentially due to the nature of the wireless medium that is very sensitive to the surrounding environment and to the possible simultaneous multiple accesses to the medium by the different sensor nodes. In this paper, we propose a wireless solution based on the physical layer of IEEE 802.15.4 standard in the 2.4 GHz frequency band that enhances packet delivery ratio under an acceptable end-to-end delay threshold during all phases of the launching operation. The proposal is a multi-channel and multi-hop protocol that allows sensors that are deployed close to the interstage of the HLV to communicate with a multi-radio interface concentrator node. Simulation results show promising performance in terms of packet delivery rate and end-to-end delay. Highlights: Using wireless communications on board Heavy-Lift Launch Vehicles has many benefits. Multi-channel and multi-radio techniques enhance network performance significantly. The use of mesh communications increases connectivity and robustness. Simulation results show that WSNs deployed on HLVs can answer application needs.